The effect of recycle water quality on the flotation of a Platreef ore - Peku, Zandile (Department of Chemical Engineering, 2024)
One of the major challenges facing mining houses today is to come up with strategies to maximize water resource utilisation. Water is a scarce resource, and every opportunity must be explored to maximize water conservation. Mining operations consume a lot of water for many activities including mineral processing, slurry transport, dust suppression and employee requirements. Apart from mining (3%), there are other competing demands for water from other sectors, for example, the municipal (6.1%), agricultural (62%), energy (2%), forestry (3%), industrial sectors (3%), and domestic (27%) (Askham & Van der Poll, 2017). There is therefore a need for the mining sector to reassess its water usage with a view to not only understanding water footprint but also ensuring maximum water resource utilization. Mining operations not only consume a lot of water but also pose serious environmental hazards associated with tailings disposal, effluent discharge, and release of process water into the water table. The wastewater produced in mineral processing contains a lot of suspended solid particles, heavy metal ions, residual flotation reagents, organics, and other pollutants. Most plants have on-site wastewater treatment plants to treat the effluent before recycling it back to the mineral processing plant (Park et al., Han & Ji, 2018). This practice is expensive due to the need to procure water treatment equipment and chemicals. Some researchers have proposed the development of closed-circuit operation approaches where the process water is recycled within the mineral processing plant. The effects of recycling process water are ore specific, i.e., each ore will respond differently to different water chemistries. Little research has been conducted to understand the effect of different specific ions and their concentrations on the Platreef ore. With the depletion of the Merensky and UG2 ore, mining houses are shifting their attention to the Platreef ore as an alternative platinum group metal resource. The timing of this project therefore becomes critical as new Platreef mines are being opened in South Africa according to Jacobsen (2021). Studies by Boujounoui et al. (2015) show that increasing use of recycle water in flotation ores has negative effects on recovery and grade of the valuable minerals. These have been traced to the accumulation of dissolved compounds, inorganic and organic, which alter the chemistry of the system. However, some studies like Dzingai et al., (2020), Corin et al., (2011) etc. have indicated positive process benefits arising by recycling of process water. For example, an increase in the ionic strength of water has been shown to result in increased water recovery, solids recovery without affecting the grade in a sulphidic platinum group metal ores. This study therefore sought to investigate the effect of process water recycling (with focus on specific ions) on the flotation of the Platreef ore. The concentrations or window of concentrations beyond which the specific ions cause the flotation performance of the Platreef ore begins to decline have also be determined. The study has shown that increasing the ionic strength of process water had a corresponding increase in the water recovery while the solids recovery did not always follow the same pattern. The spiking of ions at different concentrations was used to determine which ions were beneficial to the flotation process and which ones were deleterious. It was also noted shown that Cu flotation only improved in the presence of Ca2+ ions. When other ions were introduced in the system the copper flotation was negatively affected because the copper grade and recovery were lower compared 3 SPW (synthetic plant water). Generally, the presence of the selected ions in synthetic process water improved the recovery of all the valuable minerals with the exception of nickel at 800 ppm Mg2+. This study on recycling water usage in flotation serves as a contribution to ensuring a lower usage of potable water in floating the Platreef ore.